Chrysanthemum zawadskii ethanol extract inhibits the replication of alpha-coronavirus and beta-coronavirus - Chansoo Kim; Jang Hoon Kim; Siyun Lee; Chunghyeon Lee; Gwi Yeong Jang; Jihun Choi; WooChul Jung; Jayhyun Park; Junsoo Park (PLoS ONE, 2025)
Coronavirus can induce various diseases, from mild common cold to severe COVID-19. Coronavirus can be continuously prevalent, similar to the influenza virus, due to its frequent mutation of the RNA genome. Therefore, diverse methods are required to treat coronavirus-related diseases. Chrysanthemum zawadskii, found in Asian countries including Korea, has been traditionally used to treat various diseases, including cough, pneumonia, and common cold. However, the antiviral effects of Chrysanthemum zawadskii have not been reported yet. Here, we demonstrated that Chrysanthemum zawadskii ethanol extract (CZE) treatment interferes with the replication of alpha-coronavirus (HCoV-229E) and beta-coronavirus (HCoV-OC43). CZE treatment ameliorates beta-coronavirus-induced cytotoxicity and reduces plaque formation. CZE treatment inhibits the coronavirus protein and RNA expression, indicating CZE inhibits coronavirus replication. HPLC analysis showed that CZE contains many antiviral compounds, such as luteolin and isochlorogenic acid. These results indicate that CZE is a potent medicinal herb for treating coronavirus-related diseases.